Atomic Structure and Its Connection to The Quranic Verses' Context - Abdul Mujala; Muhammad Reza; Kana Puspita (Elkawnie, 2023)
Abstract: The growth of science in the twenty-first century, particularly in chemistry, is critically dependent on the integration of science and the Qur'an. Since numerous verses in the Qur'an disclose the fundamental principles of chemistry, such as the size of an atom, the integration of science and the Qur'an is nothing new in modern science, especially chemistry. As a result, this article will go into further detail regarding the atomic structure's physical setting and how it relates to Qur'anic verses. Writing this paper involved conducting literature searches on both contemporary science and Qur'anic interpretations of atomic structure. The word "dzarrah" appears in QS Az-Zalzalah verses 7-8, An-Nisa verse 40, and Yunus verse 61, and is interpreted as the size of a mustard seed that the human intellect may yet attain. However, "dzarrah" is often frequently interpreted as atomic size, since the atomic radius of the smallest atom (Hydrogen) and biggest atom (Organesson) atoms are 1.2 x 10-10 m and 1.52 x 10-10 m, respectively, with 1 million being smaller than the radius of mustard seed (5 x 10-4 m). Thus, the word dzarrah, which is translated as the size of a mustard seed, is less proportional to describe a much smaller atomic size. This atomic scale later served as a precursor for new developments in chemical research, such as nanomaterials and quantum dots.Abstrak: Integrasi sains dan Al-Qur’an menjadi dasar yang penting untuk pengembangan ilmu sains pada abad ke-21, khususnya dalam ilmu kimia. Integrasi sains dengan Al-Qur’an sebetulnya bukanlah hal baru dalam sains modern, khususnya kimia, karena ada banyak ayat-ayat Al-Qur’an yang mengungkapkan tentang konsep dasar kimia, misalnya ukuran atom. Oleh karena itu, artikel ini akan membahas secara lebih jelas tentang konteks materi struktur atom dan kaitannya dengan ayat-ayat Al-Qur’an. Metode penulisan artikel ini menggunakan kajian literatur, baik itu dari segi sains modern dan tafsir Al-Qur’an tentang struktur atom. Kata “dzarrah” muncul dalam QS Az-Zalzalah ayat 7-8, QS An-Nisa ayat 40, dan QS Yunus ayat 61, yang ditafsirkan seukuran biji sawi yang ukurannya masih dapat dijangkau oleh pikiran manusia. Namun, “dzarrah” juga kerap diterjemahkan seukuran atom, padahal jari-jari 1 atom paling kecil (Hidrogen) dan paling besar (Organesson) berturut-turut adalah 1,2 x 10-10 m dan 1,52 x 10-10 m, dimana 1 juta lebih kecil dari jari-jari biji sawi (5 x 10-4 m). Sehingga kata dzarrah yang diterjemahkan sebagai ukuran biji sawi kurang proporsional untuk menggambarkan ukuran atom yang jauh lebih kecil. Ukuran atom ini kemudian menjadi cikal bakal perkembangan penelitian di bidang kimia, misalnya nanomaterial dan quantum dots.